Geographical differences in cancer treatment and survival for patients with oesophageal and gastro‐oesophageal junctional cancers. Issue 11 (2nd June 2020) - Jestin Hannan, C.; Linder, G.; Kung, C.‐H.; Johansson, J.; Lindblad, M.; Hedberg, J.
Abstract : Background: Only around one‐quarter of patients with cancer of the oesophagus and the gastro‐oesophageal junction (GOJ) undergo surgical resection. This population‐based study investigated the rates of treatment with curative intent and resection, and their association with survival. Methods: Patients diagnosed with oesophageal and GOJ cancer between 2006 and 2015 in Sweden were identified from the National Register for Oesophageal and Gastric Cancer (NREV). The NREV was cross‐linked with several national registries to obtain information on additional exposures. The annual proportion of patients undergoing treatment with curative intent and surgical resection in each county was calculated, and the counties divided into groups with low, intermediate and high rates. Treatment with curative intent was defined as definitive chemoradiation therapy or surgery, with or without neoadjuvant oncological treatment. Overall survival was analysed using a multilevel model based on county of residence at the time of diagnosis. Results: Some 5959 patients were included, of whom 1503 (25·2 per cent) underwent surgery. Median overall survival after diagnosis was 7·7, 8·8 and 11·1 months respectively in counties with low, intermediate and high rates of treatment with curative intent. Corresponding survival times for the surgical resection groups were 7·4, 9·3 and 11·0 months. In the multivariable analysis, a higher rate of treatment with curative intent (time ratio 1·17, 95 per cent c.i. 1·05 to 1·30; P < 0·001) and a higher resection rate (time ratio 1·24, 1·12 to 1·37; P < 0·001) were associated with improved survival after adjustment for relevant confounders. Conclusion: Patients diagnosed in counties with higher rates of treatment with curative intent and higher rates of surgery had better survival. Abstract : This national cohort study of 5959 patients with oesophageal and gastro‐oesophageal junction (GOJ) cancer showed improved survival for patients in counties with a higher rate of treatment with curative intent and higher resection rate. Explanation needed Abstract : Antecedentes: En los pacientes con cáncer en el esófago y de la unión gastroesofágica ( gastroesophageal junction, GOJ), solamente en una cuarta parte se practica una resección quirúrgica. Este estudio de base poblacional analizó las tasas de tratamiento con intención curativa y de resección y su asociación con la supervivencia. Métodos: A partir del Registro Nacional Sueco de Cáncer de Esófago y Estómago ( National Register for Oesophageal and Gastric Cancer, NREV), se identificaron los pacientes diagnosticados de cáncer de esófago y de la GOJ entre 2006‐2015. El NREV se cruzó con otros registros nacionales para obtener información adicional. Se calculó la proporción anual de pacientes tratados con intención curativa o mediante resección quirúrgica en cada una de las áreas territoriales de los condados y se categorizaron en baja, intermedia y alta. El tratamiento con intención curativa se definió como la quimiorradioterapia definitiva ( definitive chemoradiation therapy, dCRT) o la cirugía, con o sin tratamiento oncológico neoadyuvante. Se analizó la supervivencia global con un modelo multinivel basado en el condado de residencia en el momento del diagnóstico. Resultados: Se incluyeron 5.959 pacientes, de los que 1.503 (25, 2%) fueron tratados quirúrgicamente. La mediana de supervivencia global después del tratamiento con intención curativa fue de 7, 7, 8, 8 y 11, 1 meses para los condados de volumen bajo, intermedio y alto. Para el grupo de cirugía fue de 7, 4, 9, 3 y 11, 0 meses, respectivamente. En el análisis multivariable, una mayor tasa de tratamiento con intención curativa y una mayor tasa de resección se asociaron con una mejor supervivencia (tiempo ganado 1, 17; i.c. del 95% 1, 05‐1, 30, P < 0, 001 y tiempo ganado 1, 24; i.c. del 95% 1, 12‐1, 37, P < 0, 001) después del ajuste para los factores principales de confusión. Conclusión: Los pacientes diagnosticados en condados con tasas altas de tratamiento con intención curativa y de cirugía tuvieron una mejor supervivencia.